Enhanced Fluoride Release from Glass Ionomer Cements and Compomers Modified with Clove Oil and Thymol: A Step Toward Advanced Caries Prevention - Haider, Shajia; Abidi, Yawar Ali; Ahmad, Affan; Islam, Fareeda; Batool, Aeliya; Raza, Syed Saqib (Indus Journal of Bioscience Research, 2025)
Dental caries, a prevalent global health issue, significantly impacts oral health and quality of life. Glass ionomer cements (GICs) and compomers, valued for their fluoride-releasing properties, are pivotal in caries prevention and management. This study explores the enhancement of fluoride release from GICs and compomers modified with natural additives—clove oil and thymol—at varying concentrations (0.5%, 1%, 2%). These additives, known for their bioactive and antimicrobial properties, were incorporated into the dental materials, and fluoride release was measured over 30 days. Disc-shaped specimens were fabricated, standardized, and tested for fluoride ion release at predetermined intervals (Days 1, 7, 14, 30) using an ion-selective electrode. Results revealed that modified materials exhibited significantly higher fluoride release compared to unmodified controls. The 2% clove oil and thymol-modified samples demonstrated the greatest cumulative fluoride release, with a dose-dependent effect observed across concentrations. Statistical analysis confirmed significant differences (p < 0.05) between control and modified groups, indicating that natural additives enhance fluoride release properties effectively. The findings underscore the potential of clove oil and thymol in improving the therapeutic efficacy of dental materials, with implications for sustained caries prevention. By combining fluoride delivery with the bioactive benefits of natural additives, this study provides a pathway for developing advanced restorative materials to address oral health disparities, especially in high-risk populations. Future research should focus on optimizing these materials for broader clinical application, ensuring enhanced fluoride release without compromising structural and functional integrity.